The effectiveness of learning media based on the guided inquiry model to improve students science literature skills and scientific attitudes - Anita Kintan Pratiwi; Muh. Makhrus; Muhammad Zuhdi (Jurnal Pijar Mipa, 2021)
The study aims to determine the effectiveness of physics learning media based on the guided inquiry learning model to improve students' science literacy skills and scientific attitudes effectively and efficiently.ÃÂ  The type of the research is a Research and Development (R&D) which adopts the 4D model. The effectiveness obtained from the limited trial which was used to get the value of the N-gain test and the efficiency was determined from the students' responses and the results of the scientific attitude questionnaire. The results of the study based on the results of the N-gain test obtained an average value of 0.55 with a medium category. Student responses indicated that they are not satisfied with online learning and the results of the scientific attitude response questionnaire showed that there is an increase in students' scientific attitudes. So it can be concluded that the effectiveness of the physics learning media based on the guided inquiry learning media on material of momentum and impulse is effective and efficient to improve students' scientific literacy skills and scientific attitudes.